SOX4, SOX11 and PAX6 mRNA expression was identified as a (prognostic) marker for the aggressiveness of neuroendocrine tumors of the lung by using next-generation expression analysis (NanoString). (April 2015) - Walter, Robert Fred Henry; Mairinger, Fabian Dominik; Werner, Robert; Ting, Saskia; Vollbrecht, Claudia; Theegarten, Dirk; Christoph, Daniel Christian; Zarogoulidis, Konstantinos; Schmid, Kurt Werner; Zarogoulidis, Paul; Wohlschlaeger, Jeremias
ABSTRACT : Background: Neuroendocrine tumors of the lung (NELC) account for 25% of all lung cancer cases and transcription factors may drive dedifferentiation of these tumors. This study was conducted to identify supportive diagnostic and prognostic biomarkers.Materials & methods: A total of 16 TC, 13 AC, 16 large cell neuroendocrine carcinomas and 15 small cell lung cancer were investigated for the mRNA expression of 11 transcription factors and related genes ( MYB, MYBBP1A, OCT4, PAX6, PCDHB, RBP1, SDCBP, SOX2, SOX4, SOX11, TEAD2 ).Results: SOX4 (p = 0.0002), SOX11 (p < 0.0001) and PAX6 (p = 0.0002) were significant for tumor type. Elevated PAX6 and SOX11 expression correlated with poor outcome in large cell neuroendocrine carcinomas and small cell lung cancer (p < 0.0001 and p = 0.0232, respectively) based on survival data of 34 patients (57%).Conclusion: Aggressiveness of NELC correlated with increasing expression of transcription factors. SOX11 seems to be a highly valuable diagnostic and prognostic marker for aggressive NELC.